The HPA axis in bipolar disorder: Systematic review and meta-analysis - Belvederi Murri, Martino; Prestia, Davide; Mondelli, Valeria; Pariante, Carmine; Patti, Sara; Olivieri, Benedetta; Arzani, Costanza; Masotti, Mattia; Respino, Matteo; Antonioli, Marco; Vassallo, Linda; Serafini, Gianluca; et al. (Psychoneuroendocrinology, 2016)
•Bipolar disorder is associated with state and trait hyperactivity of the HPA axis.•Abnormalities of glucocorticoid signaling are found in several key brain areas.•Cortisol levels are associated with structural and functional neuroimaging indices in BD.•HPA axis dysregulation is not a endophenotype of bipolar disorder.•HPA axis dysfunction can increase the risk of relapses and cognitive deterioration. To provide a quantitative and qualitative synthesis of the available evidence on the role of Hypothalamic–Pituitary–Adrenal (HPA) axis in the pathophysiology of Bipolar Disorder (BD). Meta-analysis and meta-regression of case-control studies examining the levels of cortisol, ACTH, CRH levels. Systematic review of stress reactivity, genetic, molecular and neuroimaging studies related to HPA axis activity in BD. Forty-one studies were included in the meta-analyses. BD was associated with significantly increased levels of cortisol (basal and post-dexamethasone) and ACTH, but not of CRH. In the meta-regression, case-control differences in cortisol levels were positively associated with the manic phase (p=0.005) and participants’ age (p=0.08), and negatively with antipsychotics use (p=0.001). Reviewed studies suggest that BD is associated with abnormalities of stress-related molecular pathways in several brain areas. Variants of HPA axis-related genes seem not associated with a direct risk of developing BD, but with different clinical presentations. Also, studies on unaffected relatives suggest that HPA axis dysregulation is not an endophenotype of BD, but seems related to environmental risk factors, such as childhood trauma. Progressive HPA axis dysfunction is a putative mechanism that might underlie the clinical and cognitive deterioration of patients with BD. BD is associated with dysfunction of HPA axis activity, with important pathophysiological implications. Targeting HPA axis dysfunctions might be a novel strategy to improve the outcomes of BD.